CRISPR/Cas9-3NLS/sgHMGA2@PDA nanosystem is the potential efficient gene editing therapy for gastric cancer with HMGA2 high expression - Wu, Zhouying; Huo, Xue; Yang, Tingyu; Liu, Kun; Wu, Ting; Feng, Zongqi; Wang, Min; Li, Feng; Jia, Jianchao; Zhang, Xiaoran; Gao, Wenming; Yu, Lan (Frontiers in Oncology, 2022)
Gene therapy is one of the target therapies with promising clinical use for gastric cancer (GC). However, the delivery of the CRISPR/Cas9/sgRNA (RNP) gene editing tool severely limits the practical therapeutic effect of GC. Therefore, it is a great challenge to develop RNP delivery system that is simple to prepare and can rapidly encapsulate RNP while achieving high delivery and gene editing efficiency. We developed, for the first time, the CRISPR/Cas9@PDA nano-delivery system that can achieve high-efficiency delivery (95%) of CRISPR/Cas9-3NLS/sgHMGA2 and high-efficient HMGA2 gene editing (82%) of GC cells. In particular, the experiment’s weak alkaline environment can not only protect the activity of CRISPR/Cas9-3NLS/sgHMGA2, but trigger the self-polymerization of polydopamine (PDA). Meanwhile, the presence of KE in the CRISPR/Cas9 amino acid sequence can achieve the directional growth of PDA, thus forming a core-shell structure that protects the CRISPR/Cas9-3NLS/sgHMGA2. This efficient CRISPR/Cas9-3NLS/sgHMGA2 delivery and HMGA2 gene editing ability has also been verified in mice, which can significantly inhibit tumor growth in mice. The success of building the delivery system and its ideal treating effect give hope to the efficacious treatment for the GC patients with HMGA2 high expression.